Menor enorme : ensaios sobre o pequeno na literatura - Pereira, Moema Vilela (2017)
This Thesis comprehends one book and two booklets of fiction, followed by four essays on and built on Creative Writing. The works investigate forms of short fiction as well as less central issues of literary theory and creation: the fictional works and the essays discuss short-short story and minifiction, gestures and the notes of a writer. The longest essay examines the contemporary theorization about minifiction, relating Hispanic American authors, to trace and problematize options for terminology, genre relations, formal, structural, and pragmatic characteristics. It also observes the consequence produced by the theoretical perspectives chosen to address these mentioned forms. On the other hand, the essays on notes and gestures develop examples for a theoretical-critical proposal within Creative Writing; the first case affiliated to the personal essay, a contemporary descendant of Montaigne, and the latter to the writing manual, teaching aspiring writers technical artifices and analyzing its different effects based on concrete cases. This Thesis presents artistic Creative Writing and theoretical Creative Writing works, for examining different possibilities within this relatively new research area in Brazil at PhD level, and the intersections of theory, criticism and creation.